2009
DOI: 10.1007/s10745-009-9293-7
|View full text |Cite
|
Sign up to set email alerts
|

Using Weed Control Knowledge from Declining Agricultural Communities in Invasive-Species Management

Abstract: Traditional and small-scale farmers may know of practices that control weedy species. When these species are also problematic in restored or managed areas, a collection of this knowledge might assist control efforts. However, past criticisms of using local ecological knowledge (LEK) from small-scale farmers state that small sample sizes and highly variable responses among informants hinders LEK's utility in management. Here I document weed-control knowledge held by New Jersey salt-hay farmers to control common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…However, our study did not specifically assess the content of the knowledge. Finding effective knowledge is not similar to finding commonly held knowledge (Bart 2010 ). Effective knowledge might be limited to a few farmers who are members of a pineapple growers association and have in general adequate information.…”
Section: Discussionmentioning
confidence: 97%
“…However, our study did not specifically assess the content of the knowledge. Finding effective knowledge is not similar to finding commonly held knowledge (Bart 2010 ). Effective knowledge might be limited to a few farmers who are members of a pineapple growers association and have in general adequate information.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have relied on as few as one (Seoane et al 2005) or two experts (Clevenger et al 2002) and it is common to use less than ten participants (e.g., Smith and Wilkinson 2002, Pollock et al 2007, Pullinger and Johnson 2010. Especially in cases when exceptionally local knowledge is required, only very few individuals may posses this knowledge and sample size may be irrelevant as long as one knowledgeable expert is involved (Bart 2010).…”
Section: Bias Uncertainty and Aggregation Of Expert Knowledgementioning
confidence: 99%
“…Indeed, a number of studies have questioned the reliability of TEK data. Bart (2010) for example, revealed that farmer accounts of TEK (how Phragmites − a wetland grass − responds to cessation of burning) were contradictory, ranging from stopping invasion to accelerating invasion. Don (2010) in observing that applying TEK to environmental management policy is problematic because it contains accurate and inaccurate information, asks why not simply apply scientific knowledge from the start?…”
Section: Introductionmentioning
confidence: 99%
“…Critically they contend that to prevent it becoming incorporated into ecological studies as a token reference to local communities TEK should be "scrutinised as other information is scrutinised." Bart (2010) similarly notes that for it to be useful in restoration ecology, researchers need to be more concerned about the validity of the knowledge.…”
Section: Introductionmentioning
confidence: 99%